Histories of Ethos: World Perspectives on Rhetoric - Baumlin, James S.; Meyer, Craig A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The essays in this collection aim to waken contemporary discussions of ethos(and of rhetoric generally) from their Western, classical-Aristotelian slumbers.Western rhetoric was never univocal in its theory or practice of ethos: the essaysin this collection provide proof of this. The contributors aimed to shake rhetoricout of its Eurocentrism: the traditions of Africa, the Middle East, and Asia sustaintheir own models of ethos and lead us to reconsider rhetoric in its richvariety-what ethos was, is, and will become. This collection is groundbreakingin its attempt to outline the diversity of argument, trust, and authority beyonda singular, dominant perspective.This collection offers readers a choice of itineraries: thematic, geographic, andhistorical. Essays may be read individually or cumulatively, as exercises incomparative rhetoric. In taking a world perspective, Histories of Ethos willprove a seminal discussion. Its comparative approach will help readers appreciatethe commonalities and the distinctions in competing cultural-discursivepractices-in what brings us together and what drives us apart as communities.Additionally, it is the editors' hope that, out of this historical, multiculturaldialogue, some new perspectives on ethos may come forward to broaden ourdiscussion and reach of understanding.